2021
DOI: 10.1186/s12885-021-08387-2
|View full text |Cite
|
Sign up to set email alerts
|

Assessing service availability and readiness to manage cervical cancer in Bangladesh

Abstract: Background The second most common cancer among females in Bangladesh is cervical cancer. The national strategy for cervical cancer needs monitoring to ensure that patients have access to care. In order to provide accurate information to policymakers in Bangladesh and other low and middle income countries, it is vital to assess current service availability and readiness to manage cervical cancer at health facilities in Bangladesh. Methods An intervi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 9 publications
0
17
0
Order By: Relevance
“…With reference from previous studies assessing health facilities' readiness in services delivery, 70% GSR score was considered to be the cut-off point, where facilities that scored 70% or higher were considered to be ready to offer the expected health services. [31,32,42,43] In this study, the GSR index of 87%, is above the threshold, implying that the health facilities in the study area are generally ready for health services delivery. A report from the Ministry of Health [24] on service availability and readiness assessment conducted in 27 districts of Tanzania found that the private facilities including faith-based ones, had higher scores on the GSR index than the government facilities.…”
Section: Health Facilities' General Service Readiness For Health Serv...mentioning
confidence: 57%
See 2 more Smart Citations
“…With reference from previous studies assessing health facilities' readiness in services delivery, 70% GSR score was considered to be the cut-off point, where facilities that scored 70% or higher were considered to be ready to offer the expected health services. [31,32,42,43] In this study, the GSR index of 87%, is above the threshold, implying that the health facilities in the study area are generally ready for health services delivery. A report from the Ministry of Health [24] on service availability and readiness assessment conducted in 27 districts of Tanzania found that the private facilities including faith-based ones, had higher scores on the GSR index than the government facilities.…”
Section: Health Facilities' General Service Readiness For Health Serv...mentioning
confidence: 57%
“…Considering the number of components available, scores for each domain were obtained before computing the composite mean of the scores of the five domains for the aggregate GSR index. [29] Based on previous studies, [31,32] the general service readiness scores were compared with the benchmark of 70%, where facilities/areas scoring above were considered to be ready to provide the services.…”
Section: Measurement Of Variablesmentioning
confidence: 99%
See 1 more Smart Citation
“…The interviews were conducted in-person and were recorded for further analysis. The details of the data collection method have been fully described in studies by Paromita and Rakhshanda [ 18 , 19 ].…”
Section: Methodsmentioning
confidence: 99%
“…Indices were stratified by facility level and compared to a RI cutoff score of 70%. This cutoff was based upon a study conducted by Wilbroad Mutale et al in Zambia utilizing the SARA tool, which considered a facility to be ‘ready’ to manage diabetes care if it scored above 70% [ 18 , 19 , 21 ]. All data were analyzed using SPSS version 21 (SPSS, Chicago, IL).…”
Section: Methodsmentioning
confidence: 99%